Pengaruh intellectual capital terhadap market value pada perusahaan telekomunikasi yang terdaftar di Bursa Efek Indonesia tahun 2006-2011 - Psp, Doni Diwaf; Efni, Yulia; Wijaya, Errin Yani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study examined the effect of Intellectual Capital (IC) on financial performance. the variable is the Human Capital Efficiency (HCE), Structural Capital Efficiency (SCE) and Customer Capital Efficiency (CCE) to variable Market to Book Value (MB).The population on this research is the entire of telecommunications sector companies that have go public and listed on the Indonesia Stock Exchange (IDX) during the period of 2006-2011. The sampling technique used was a saturated sampling (census) population in which all members of the research sample. Obtained a total sample of 5 companies. The analysis technique used is multiple regression analysis with the least squares equation, hypothesis testing using the t-statistic and f-statistic with a significance level of 5%, and also performed classical assumption.The results showed that the variables of intellectual capital (human capital, structural capital and customer capital) significantly jointly (simultaneously) to the market value. While partially indicates that the variable Human Capital Efficiency (HCE) and no significant negative effect on Market Value (MB).Keywords: intellectual capital, human capital, structural capital, customer capital, market value.